Vaginal hysterectomy, vaginal salpingoophorectomy and uterosacral ligament colpopexy: a view from above (in English and Spanish). (January 2017) - Siff, Lauren; Jallad, Karl; Pizarro-Berdichevsky, Javier; Walters, Mark
Abstract Aim of the video The aim of this video is to make vaginal hysterectomy (TVH), vaginal salpingoophorectomy and uterosacral ligament (USL) colpopexy approachable by showing the key procedural steps from both the vaginal and abdominal perspectives. Methods This production shows TVH with salpingoophorectomy and USL colpopexy that was performed on a cadaver and filmed simultaneously from the vaginal and abdominal views. The video begins with an anatomy overview from the open abdomen and proceeds with the TVH. The anterior and posterior peritoneal entries, a technique to safely and easily access the adnexa, as well as the placement of USL suspension sutures are highlighted. The proximity of the ureter and its distance from the three locations most vulnerable to injury during this procedure (the uterine artery pedicle, the infundibulopelvic ligament and the USL) are illustrated. The location of the USL suspension sutures in relation to the ischial spine, the rectum and the sacrum are demonstrated. For all of these crucial steps, a series of picture-in-picture views simultaneously showing the abdominal and vaginal perspectives are presented so that the viewer may better understand the spatial anatomy. Conclusion This video provides the viewer with a unique anatomic perspective and helps more confidently perform TVH, vaginal salpingooophorectomy and USL colpopexy.